Vaginal bacterial diversity from healthy gilts and pregnant sows subjected to natural mating or artificial insemination - Torres Luque, Andrea (2021)
The profitability of commercial pig farms largely depends on the reproductive performance of gilts and sows. The aim of this study was to identify differences in the composition and diversity of vaginal microbiota between gilts (G) and pregnant (P) sows, both artificially inseminated (AI) and natural mated (NM). Samples were collected by scraping the vaginal mucosa of G (n = 10) and P (NM, n = 10 and AI, n = 7) sows. Samples were analysed by culture-dependent techniques and 16S-rRNA gene High-Throughput-Sequencing. The profiles of the cultured microbiota showed two distinctive clusters, one of them grouped four samples of P sows from the AI group. The vaginal microbiota from P had lower richness than G sows (Mann-Whitney/Kruskal-Wallis test, p < 0.01), but all vaginal samples had a similar diversity. The PERMANOVA analyses revealed significant differences (p < 0.01) between the microbial communities' structures from G and P sows. The bacteria phyla with the highest relative abundances was Proteobacteria (33.1%), followed by Firmicutes (32%), Cyanobacteria (13.3%) and Actinobacteria (13.2%). The relative abundance for phyla, families and genera was estimated and Proteobacteria was significantly higher (p = 0.038) in P than in G sows; Firmicutes was significantly lower in AI than G and NM sows. A “core microbiota” included Lactobacillus, Bacillus, Enterococcus, Acinetobacter, and Pseudomonas. The results presented highlight the differences in the bacterial composition between G and P sows, as well as the changes in the microbial populations associated with the breeding method.